The Role of the Madrasah Committee in Achieving Islamic Education Goals at Madrasah Tsanawiyah As’adiyah - Tahir, Muhyiddin; Tang, Muhammad; Muhsyanur, Muhsyanur (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This study explores the role of the Madrasah Committee in achieving the goals of Islamic Education at Madrasah Tsanawiyah As’adiyah No. 3 Atapange. The research examines the committee's involvement in policy-making, providing intellectual and financial support, overseeing ethical programs, and facilitating students' needs. It also investigates the level of achievement of Islamic education goals, which include fostering moral behavior towards Allah SWT, fellow humans, oneself, and the environment. The study employs a qualitative approach with sociological and psychological methods, utilizing observation, interviews, and documentation to gather data. The findings reveal that the Madrasah Committee plays a significant role in supporting Islamic education, particularly in guiding students’ religious practices, ethical conduct, discipline, and environmental awareness. These contributions are integral to achieving the intended educational outcomes, including the development of students' religious and ethical values. The research emphasizes the importance of the Madrasah Committee’s active participation in the educational process, highlighting their impact on the success of Islamic education at the institution.